Regulatory Requirements of In Process Content Uniformity - A Practical Approach - KATHIRESAN, K.; SRINIVASAN, R.; KANNAN, K.; PANDIAN, P.; SELVAMUTHUKUMAR, S.; MANAVALAN, R. (Asian Journal of Chemistry, 2010)
Blending is one of the most important unit operations in preparation of tablets and the end point of this process to be evaluated by sampling the blend and performing the offline analysis. These schedules are made in order to establish the uniformity and homogeneity of the blend and provide a platform for the validity. It gives a degree of confidence that the blend when compressed into tablet will give an output of uniform dosage units. These schedules were used only to provide confidence in the processing. However, today with the advent of theories such as process capabilities and the lesser importance to retrospective validation and more learning towards continual validated state, the need to shift strategies are prevalent. The FDA guidance on content uniformity 2003 provides such a platform. The guidance is being widely used in the assessment during the processing of exhibit/submission batches since 2004. This is the first time that the guidance has been employed for commercial product also. The primary objective of this project work is to asses the blend uniformity with three validation batches and establishing the adequacy of mixing for the product. To prove that the data of blending and compression is uniform and the process of blending and compression is within the control from the batches manufactured commercially.